O Desenvolvimento do Talento: Relatório de Estágio Profissionalizante realizado na equipa de sub-19 da Associação Académica de Coimbra / OAF, SDUQ - Bruno Domingues Pereira (2018)
This report was prepared based on the organization of under-19 of the Associação Académica de Coimbra / Organismo Autónomo de Futebol. This historical institution presents as concern the sporty and social development of the player.The main purpose of this report is to describe and reflect about lived experiencies throughout the internship process. Currently, the Soccer Young Training Department aims to develop the players for them to achieve high performance. In this sense, given the context in which the internship was accomplished, it becomes relevant to develop the theme of talent.In this context, the review of the literature has some important conclusions: talent is a complex and potential value concept; talent is the consequence of an adequate, intense and prolonged in time development process; training and learning are determining factors for the training of children and young people, in the sense of talent development to achieve high performance.In the framework of the professional practice consummated consider the following considerations: the idea of the game from the coach must aline with the philosophy of the club, mainly, when the goal is the empowerment of the player; the principles and sub-principles of the game underlying the game model are fundamental, while training process guide; the standard morphocycle has a huge importance, offering logic to the process and ensuring the possibility of the collective and individual development; the training exercise is fundamental and must represent the fluidity that characterizes the game.In conclusion of the study carried out, it is important that the Soccer Young Training Department has a quality internal structure and organization. Quality that comes from the work of a competent and experienced team in the training of children and young people directed to the high income, work sustained in a coherent metodology with the goal of the department, in the way of talent development.